Integrated coal pyrolysis with dry reforming of low carbon alkane over Ni/La2O3 to improve tar yield. (15th April 2020) - Lv, Jiannan; Wang, Dechao; Wang, Mingyi; Li, Yang; Jin, Lijun; Hu, Haoquan
Graphical abstract: Highlights: Integrated coal pyrolysis with dry reforming of alkane (DRA) can improve tar yield. Ni/La2 O3 prepared by co-precipitation shows good performance for DRA. The highest tar yield is 20.6 wt.% in coal pyrolysis with DRA over Ni/La2 O3 . La2 O2 CO3 formed from La2 O3 inhibits carbon deposition during DRA reaction. Abstract: Integrated coal pyrolysis with dry reforming of methane with addition of low carbon alkane provides an effective method for improving tar yield. One of the key issues is the development of catalysts for dry reforming of low carbon alkane (DRA). In this study, Ni/La2 O3 was prepared by co-precipitation and used for DRA. A mixture of ethane and methane in molar ratio of 1:8 was reformed by CO2 and integrated with coal pyrolysis to improve tar yield. The result showed that tar yield under integrated process of coal pyrolysis with DRA over Ni/La2 O3 at 600 °C is 1.18 times that under N2 . Ni/La2 O3 shows less carbon deposition, and better performance than Ni/Al2 O3, and the tar yield over Ni/La2 O3 is 1.09 times that over Ni/Al2 O3 at 600 °C. Less carbon deposition over Ni/La2 O3 is mainly due to the formation of La2 O2 CO3 under dry reforming. The tar yield remains stable after the Ni/La2 O3 was used for 6 times, indicating good regenerability of Ni/La2 O3 .